Activation of Electrophile/Nucleophile Pair by a Nucleophilic and Electrophilic Solvation in a SNAr Reaction - Sánchez, Bruno; Calderón, Cristian; Tapia, Ricardo A.; Contreras, Renato; Campodónico, Paola R. (Frontiers in Chemistry, 2018)
The nucleophilic aromatic substitution reactions of 4-chloroquinazoline towards aniline and hydrazine were used as a model system to experimentally show that a substrate bearing heteroatoms on the aromatic ring as substituent is able to establish intramolecular hydrogen bond which may be activated by the reaction media and/or the nature of the nucleophile.